Preparation and evaluation of a methyl-PEG2000-DSPE-PVP-LDC nanomaterial: A novel lidocaine delivery system - Wan-Yi Mo; Jing-Ran Kong; Hang Dai; De-Cheng Liu; Yi-Min Wang; Tuck Yun Cheang; Hui Yao; Hui Zhang (AIP Advances)
This study investigates the potential of methyl-PEG2000-DSPE-PVP-LDC as a drug delivery nanocarrier and its impact on human immortalized keratinocytes, focusing on cytotoxicity, migration inhibition, and drug-loading efficiency. Synthesized nanoparticles were characterized using scanning electron microscopy, transmission electron microscopy, zeta potential analysis, and Fourier-transform infrared spectroscopy (FTIR). The cytotoxicity in human keratinocyte HaCaT cells and the inhibition of cell migration were analyzed using a scratch assay. Furthermore, the drug-loading efficiency of the nanoparticles was quantified. The synthesized nanoparticles exhibited dimensions under 50 nm, with an optimal size of ∼10 nm for efficient drug loading. The zeta potential was −24.33 ± 2.654 mV. The drug-loading capacity was 226.618 35 µg LDC/mg nanoparticle material. FTIR revealed an interaction between lidocaine and the nanospheres. Cytotoxicity assays indicated that the nanomaterial suppressed the cell cycle progression. In addition, the nanomaterial exhibited a notable inhibition of cell migration, resulting in reduced migration efficiency compared with the control group. Thus, the methyl-PEG2000-DSPE-PVP-LDC nanomaterial demonstrates considerable promise for drug delivery owing to its small particle size, efficient drug-loading capability, and potential to inhibit the proliferation and migration of human immortalized keratinocytes, suggesting its potential diverse biomedical applications, particularly in cancer therapy.